Construindo os (des)caminhos para o aprendizado em arte: análise metodológica de livros didáticos do PNLD 2020 - Arte - Laura Paola Ferreira (2023)
This doctoral thesis aims to analyze the methodological approaches explicitly stated in the seven collections of textbooks selected for the 2020 National Textbook Program (Programa Nacional do Livro Didático – PNLD 2020 – Arte) for the field of Art in the final years of elementary education (6th to 9th grades), to verify the guidelines presented in the Teacher’s Manual and their application in the Student’s Book. Thus, a comprehensive analysis on these textbooks has been done to bring forth the epistemological perspective as well as the guidelines listed in the PNLD – 2020 – Arte public notice used by the authors of each of the seven collections selected. Furthermore, this work also presents evidence on how the methodologies outlined by the teacher’s book are addressed in the visual arts approaches of these seven collections. As a primary methodology for this investigation, a bibliographic review, using a descriptive and reflexive qualitative approach, according to Bogdan and Biklen (1994), has been conducted. The results demonstrate the importance of the connections between the theories developed in the seven PNLD-2020 - Art collections and their application in artistic activities conveyed by the textbooks.